Les transitions démographiques du XXe siècle dans les pays en développement, des contre-exemples théoriques ? - Maria Eugenia Cosio-Zavala (Les Cahiers d’EMAM)
Demographic transitions of the twentieth century are different from previous European transitions. We analyze the different demographic transitions in Latin America. Then, in a second part, we observe the demographic trends in the Arab countries, in particular those of North Africa, and show how they are similar or different from Latin American countries. In Latin America, in the last decades, there is a very significant increase in informal unions beginning at young ages. In the countries of North Africa, it is both the rise in age at marriage and contraception that explain the decline of fertility. A major difference with Latin America is the absence of conceptions outside marriage in the countries of the Maghreb and other Arab countries. In both regions, we find Malthusianism of poverty.